(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present study aimed to find out the gender difference in the psychosocial adjustment factors of higher secondary students. Survey method with stratified random sampling technique has been followed for the present study. The Psychosocial Adjustment Scale constructed and validated by the investigator(2020) has been adapted to measure the psychosocial adjustment of higher secondary students. The total sample consists of 679 higher secondary students which include 382 male and 297 female higher secondary students. The present study revealed that there is no significant difference between male and female higher secondary students in the psychosocial adjustment factors such as, mental health, depression, self esteem, self concept, anxiety, self confidence, emotion and socio-economic status. The study further revealed that the male and female students differ significantly in the total psychosocial adjustment and psychosocial adjustment factors such as,social support and social adaptation. The female students have high level of social support, social adaptation and the total psychosocial adjustment than the male higher secondary students.